The Influence of the Value Clarification Technique (VCT) Model Assisted by Puzzle Media on Improving Tolerance Character Based on Students' Morals in Social Studies Learning in Grade IV of Elementary School - Khairat, Miftahul; Karsih, Karsih; Utomo, Erry; Satibi, Otib (UNIVERSITAS PAKUAN, 2025)
This study aims to: (1) Differences in tolerance character of students with the Value Clarification Technique (VCT) model assisted by Puzzle Media in science learning in Grade IV Elementary School and students who use conventional learning models. (2) The effect of interaction between the Value Clarification Technique (VCT) model and morality on the tolerance character of students. (3) Differences in tolerance character of students who have high morality after learning using the Value Clarification Technique (VCT) model assisted by puzzle media and conventional models. (4) Differences in tolerance character of students who have low morality after learning using the Value Clarification Technique (VCT) model assisted by puzzle media and conventional models. The research design uses a quantitative approach with a quasi-experimental method, which involves two-way analysis of variance (2x2). Based on this study, it is concluded that the Value Clarification Technique (VCT) model assisted by puzzle media is more effective in improving the tolerance character of students with high morality values. Conversely, the conventional model is more suitable for students with low morality values, because it is easier to understand without the need for active exploration